In-Game Advertising: The Effects Of Telepresence On The Attitude And Purchase Intention - Hussein, Zuhal (2011)
This study investigates the mediation impact of attitude towards telepresence on the relationship between telepresence and users’ intentions to revisit computer games and their intention to purchase advertised product brand within the game played. Moderating effect of users’ experiences on relationship between telepresence and attitude towards telepresence are also investigated. This study employs a factorial design between subjects. Experiment was carried out on 260 undergraduate students from Universiti Sains Malaysia (USM), who volunteered to participate in the Internet game playing activities.